Classroom interaction and its relationship with the motive for school achievement among a sample of secondary school students in Laghouat - FATTAM, Djameleddine (Social Sciences Journal, 2021)
The current study sought to reveal the relationship between classroom interaction and learning motivation among a sample of secondary school students in The City of Laghouat. The study was interested in detecting gender differences in both the level of motivation for learning and classroom interaction among the participants. The study was conducted on a sample of 127 students from both genders and the researcher relied on the analytical descriptive approach. The data obtained were analyzed using the (SPSS) program. The study reached many conclusions, the most important of which is that there is a positive and strong correlation between classroom interaction and learning motivation among the participants.